STABILITY-INDICATING HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY METHOD FOR DETERMINATION OF ANTIHISTAMINE DRUG AZELASTINE - Patel, Shital; Ty, Pasha (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this research was to develop a simple, precise, accurate, and stability-indicating reverse-phase high-performance liquid chromatographic method for estimation of azelastine hydrochloride (AZL) in nasal spray preparation. Methods: Chromatography was performed on a 250 mm×4.6 mm, 5-μm particle size, Waters Spherisorb CN column using (50:50 v/v) mixture of potassium dihydrogen phosphate buffer and acetonitrile as mobile phase. The detection was carried out at 290 nm and flow rate employed was 1.0 ml/min. The degradation of AZL was studied under different ICH recommended stress conditions. Results: The retention time was 4.34 min for AZL. Linearity was established in the concentration range of 5–120 μg/ml, with a correlation coefficient of 0.9996. Limit of detection (LOD) and limit of quantitation (LOQ) were found to be 0.81 μg/ml and 2.44 μg/ml, respectively. Percentage recovery was found between 99 and 102%. The values of percentage relative standard deviation (<2%) proved the high precision of the proposed method. The method was found to be robust regarding any small variation in the column temperature, pH of mobile phase, and mobile phase ratio. AZL was found stable in 5 M HCl at 80°C for 5 h, 5 M NaOH at 80°C for 5 h, 30% H2O2 at 80°C for 5 h, and in oven at 70°C for 8 h. Conclusion: The results obtained in this research work clearly proved that the proposed HPLC method for the assay of AZL in nasal spray preparation is simple, precise, specific, accurate, and stability indicating. It indicates that the method is suitable for analysis of AZL in the raw material and the pharmaceutical product without interference from excipients.